Temperature Estimation Method on Optic–Electric Composite Submarine Power Cable Based on Optical Fiber Distributed Sensing - Chao Luo; Zhitao Feng; Yihua Zhu; Yuyan Liu; Yi Zhang; Ying Zhou; Muning Zhang; Lijuan Zhao (Photonics)
The status of an optic–electric composite high-voltage submarine cable (referred to as submarine cable) can be monitored based on optical fiber-distributed sensing technology, and at the same time, no additional sensor is needed in the monitoring system. Currently, this technology is widely used in submarine cable monitoring systems. To estimate the temperatures of conductor and XLPE (cross-linked polyethylene) insulation of the submarine cable based on the ambient temperature and optical fiber temperature, the thermoelectric coupling field model of the 110 kV single-core submarine cable is established and validated. The thermoelectric coupling field models of the submarine cable with different values of ambient temperature and ampacity are built, and the influence of ambient temperature and ampacity on the temperatures of conductor, insulation and optical fiber is investigated. Furthermore, the relationship between the temperatures of the conductor and insulation and the ambient temperature and optical fiber temperature is obtained. Then, estimation formulas for temperatures of conductor and insulation of submarine cable according to ambient temperature and optical fiber temperature are obtained and preliminarily validated. This work lays the foundation for condition evaluation of the submarine cable insulation, life expectancy and maximum allowable ampacity estimation.